Contribution of calcium dysregulation to impaired coronary artery contraction in Zucker diabetic fatty rats. (30th November 2022) - Liu, Lin; Yang, Hui; Kuang, Su‐Juan; Zhang, Li; Zhou, Meng‐Yuan; Zeng, Peng; Zhang, Meng‐Zhen; Rao, Fang; Zhou, Zhi‐Ling; Deng, Chun‐Yu
Abstract: Diabetic coronary artery injury is closely associated with Ca 2+ dysregulation, although the underlying mechanism remains unclear. This study explored the role and mechanism of Ca 2+ handling in coronary artery dysfunction in type 2 diabetic rats. Zucker diabetic fatty (ZDF) rats were used as the type 2 diabetes mellitus model. The contractility of coronary artery rings induced by KCl, CaCl2, 5‐HT and U46619 was significantly lower in ZDF rats than in Zucker lean rats. Vasoconstriction induced by 5‐HT and U46619 was greatly inhibited by nifedipine. However, in the presence of 1 μM nifedipine or in the Ca 2+ ‐free KH solution containing 1 μM nifedipine, there was no difference in the vasoconstriction between Zucker lean and ZDF rats. Store‐operated calcium channels (SOCs) were not involved in coronary vasoconstriction. The downregulation of contractile proteins and the upregulation of synthesized proteins were in coronary artery smooth muscle cells (CASMCs) from ZDF rats. Metformin reversed the reduction of vasoconstriction in ZDF rats. Taken together, L‐type calcium channel is important for regulating the excitation–contraction coupling of VSMCs in coronary arteries, and dysregulation of this channel contributes to the decreased contractility of coronary arteries in T2DM.